Design, Development, and Formative Evaluation of a Tablet-Based Augmented Reality Application for Early Number Learning - Elmali, Filiz; Citak, Hatice (Taylor & Francis Inc, 2026)
Early numeracy is a strong predictor of later academic outcomes, yet many augmented reality (AR) tools for young children lack transparent design reporting. This paper presents the design, development, and formative evaluation of MAGIC, a tablet-based AR application that supporting early number learning grounded in Realistic Mathematics Education. The design followed the Hannafin-Peck model, encompassing needs analysis, iterative scenario design with expert review, development, and classroom implementation, alongside usability sessions with five teachers and six children. Usability ratings and observational data indicate positive engagement and overall usability, while identifying challenges common to preschool AR, including the need for concise instructions, developmentally appropriate pacing, and mitigating tracking disruptions caused by device movement. These findings informed targeted design refinements and a set of actionable heuristics for preschool AR design. The study contributes a transparent design pathway and practical guidance for deploying AR with young learners.
Keywords: Early childhood; augmented reality; design and development; realistic mathematics education